Homeownership, Legal Administration, And The Uncertainties Of Inheritance In South Africa's Townships: Apartheid's Legal Shadows. Issue 479 (10th February 2021) - Bolt, Maxim
Abstract: Expanded homeownership in Johannesburg's townships offered the prospect of post-apartheid formal inclusion. Yet allocation of title to former rental homes has been characterized by a profound lack of normative consensus regarding ownership or inheritance. In bitter disputes over houses, appeals to law jostle and interweave with claims in a customary register. In much regional scholarship, normative pluralism provides a point of departure for understanding disagreement of this kind. This article proposes an alternative perspective by examining how dissensus is mediated and given shape by a legal–administrative process. Law becomes inchoate in layers of bureaucratic encounter, while contested claims to custom are sharpened at the interface with bureaucracy. In South Africa, taking administration as a starting point reveals the long shadows of apartheid in concrete experiences of the law, in extra-legal understandings, and in the very terms of contestation among kin. Illuminating the little-explored topic of urban property inheritance, the perspective has broader implications for understanding inequality. Inclusion through homeownership is a form of 'adverse incorporation' marked by official opacity, diffidence regarding the law, stratifying administrative dualism, and uncertainty about the parameters of ownership and inheritance.